Zaŝita ličnyh neimuŝestvennyh prav avtorov post mortem v Respubliki Tadžikistan - Urunova, Sanavbar Vahobovna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The Author presents the issue of protection of personal copyright post mortem in Tajikistan. The analysis relates to proper legal provisions of civil code of Tajikistan and Tajikistan’s Act on protection of copyright and related rights. The Author also refers to traditional custom law of Tajikistan requiring protection of human’s rights after his death, which is executed by his close relatives, particularly children. In the end of this article the Author formulates de lege ferenda postulates in order to establish and ensure post mortem protection of personal copyright, which would be similar to the protection known by the most modern civil law codification in the world, included in civil code of Russian Federation
Keywords: personal copyright; post mortem protection; customs; law; Tajikistan; copyright law; Russian Federation